RNA editing of Filamin A pre‐mRNA regulates vascular contraction and diastolic blood pressure. (7th August 2018) - Jain, Mamta; Mann, Tomer D; Stulić, Maja; Rao, Shailaja P; Kirsch, Andrijana; Pullirsch, Dieter; Strobl, Xué; Rath, Claus; Reissig, Lukas; Moreth, Kristin; Klein‐Rodewald, Tanja; Bekeredjian, Raffi; et al.
Abstract: Epitranscriptomic events such as adenosine‐to‐inosine (A‐to‐I) RNA editing by ADAR can recode mRNAs to translate novel proteins. Editing of the mRNA that encodes actin crosslinking protein Filamin A (FLNA) mediates a Q‐to‐R transition in the interactive C‐terminal region. While FLNA editing is conserved among vertebrates, its physiological function remains unclear. Here, we show that cardiovascular tissues in humans and mice show massive editing and that FLNA RNA is the most prominent substrate. Patient‐derived RNA‐Seq data demonstrate a significant drop in FLNA editing associated with cardiovascular diseases. Using mice with only impaired FLNA editing, we observed increased vascular contraction and diastolic hypertension accompanied by increased myosin light chain phosphorylation, arterial remodeling, and left ventricular wall thickening, which eventually causes cardiac remodeling and reduced systolic output. These results demonstrate a causal relationship between RNA editing and the development of cardiovascular disease indicating that a single epitranscriptomic RNA modification can maintain cardiovascular health. Synopsis: RNA‐editing of Filamin A pre‐mRNA is decreased in human cardiac disease. A mouse model lacking this editing site shows altered smooth muscle contraction and diastolic blood pressure, illustrating that ADAR2‐dependent RNA editing plays a functional role outside the central nervous system. The Filamin A (FLNA) pre‐mRNA is subject to RNA editing with the highest rates seen in the cardiovascular system. FLNA editing rates are reduced in cardiovascular disease patients. In mice, FLNA editing controls smooth muscle contraction of the dorsal aorta. Mice deficient in FLNA editing show elevated diastolic blood pressure and cardiac remodeling. Abstract : Disrupting a single mRNA editing site in mice affects smooth muscle contraction and diastolic blood pressure, while reduced editing at the same site in human correlates with cardiac disease.